High-intensity combined strength and endurance training in women: effect of hormonal contraceptive use - Taipale, R. S.; Ihalainen, J. K.; Myllyaho, M.; Forssell, J.; Jones, J. P.; Häkkinen, K.; Kyröläinen, H. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: The use of hormonal contraceptives (HC) modifies the menstrual cycle, decreases basal levels of estrogen, and increases basal levels of sex-hormone binding globulin (SHBG). Serum concentrations of sex hormones are associated with trainability including muscle mass and strength (Häkkinen et al. 2000) while levels of SHBG affect androgen availability. We hypothesized that use of HC may negatively influence adaptations to combined strength (S) and endurance (E) training, particularly on development of strength and lean mass (LM). The purpose of this study was to examine the possible influence of HC on adaptations to 10 weeks of highintensity combined S and E training in women.